Security Analysis of Miksi – Ethereum Zero Knowledge Transaction Mixer - Kamil KACZYŃSKI (Communications of International Proceedings, 2024)
Miksi is a decentralized blockchain protocol that uses zero knowledge proofs (ZKP) and cryptographic commitments to enable anonymous transactions within a secure decentralized network. The system consists of three components: the main application (miksi.ts), the ZKP circuits (deposit and withdraw.circom), and the smart contracts (Miksi.sol, deposit-verifier.sol, and withdraw-verification.sol). Each component plays a pivotal role in the overall security of the system, and we evaluate them for common vulnerabilities such as improper input validation, reentry attacks, and weaknesses in proof verification. Through this analysis, we highlight both the strengths and potential areas for improvement in ensuring secure, anonymous cryptocurrency transactions.Keywords: Ethereum, ZKP, blockchain, DeFi, anonymity, mixer